Mengatasi Kelangkaan Tafsir Ahkam di Tengah Komunitas Penggiat Fikih Nusantara - Muhammad Ishom El-Saha (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
Study on Islamic jurisprudence in Indonesian is very vigorous and developed in accord with the dynamics of society’s life in Indonesia. Starting from the study of Islamic jurisprudence on worship, marriage and even on social life in line with the revival of shariah economy. However, although the study theme of Islamic jurisprudence is getting wider, it has not aroused the mark for the interest revival of Indonesian muslim scholars to study in depth and width about the Quranic exegesis of the law yet. This writing is made to encourage those who may concern on this issue that it is advisable to those vigorously study the Islamic jurisprudence in Indonesia redesign the pattern of the study of Islamic jurisprudence to be more systematic by emphasizing its study on the Quranic exegesis of the law. This writing explains that the study of Islamic jurisprudence using the approach of the Quranic exegesis of the law will lead to the comprehensive undertanding on the problems of Islamic jurisprudence.